2020
DOI: 10.1021/acsptsci.0c00183
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity Plays a Key Role in Controlling Viral Load in COVID-19: Mechanistic Insights from a Whole-Body Infection Dynamics Model

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a pathogen of immense public health concern. Efforts to control the disease have only proven mildly successful, and the disease will likely continue to cause excessive fatalities until effective preventative measures (such as a vaccine) are developed. To develop disease management strategies, a better understanding of SARS-CoV-2 pathogenesis and population susceptibility to infection are needed. To this end, mathematical modeling can provide a rob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 93 publications
0
23
0
Order By: Relevance
“…Variation in the time of activation of the adaptive immune response in different individuals implies that the SARS-CoV-2 virus can continue replicating and remains viable ( 31 ). In a recent study, it was found that interferons play a key role in suppressing the virus in the upper airway, while macrophages are primarily responsible for viral clearance in the lungs, mononuclear phagocyte system (MPS), and other systemic sites ( 32 ). Therefore, the rate at which lung and MPS macrophages clear the virus influences the viral load in both the lungs and the plasma ( 32 ).…”
Section: Dynamics Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in the time of activation of the adaptive immune response in different individuals implies that the SARS-CoV-2 virus can continue replicating and remains viable ( 31 ). In a recent study, it was found that interferons play a key role in suppressing the virus in the upper airway, while macrophages are primarily responsible for viral clearance in the lungs, mononuclear phagocyte system (MPS), and other systemic sites ( 32 ). Therefore, the rate at which lung and MPS macrophages clear the virus influences the viral load in both the lungs and the plasma ( 32 ).…”
Section: Dynamics Of Sars-cov-2mentioning
confidence: 99%
“…In a recent study, it was found that interferons play a key role in suppressing the virus in the upper airway, while macrophages are primarily responsible for viral clearance in the lungs, mononuclear phagocyte system (MPS), and other systemic sites ( 32 ). Therefore, the rate at which lung and MPS macrophages clear the virus influences the viral load in both the lungs and the plasma ( 32 ). In patients with defective immune systems, viral clearance will depend on the excretion of the virus through the bile duct, which can take weeks.…”
Section: Dynamics Of Sars-cov-2mentioning
confidence: 99%
“…Predicted by these models, the virus population peak around symptom onset and its subsequent decay are the main elements of heterogeneous disease kinetics. A larger and detailed full-scale model [61] simulates the viral infection dynamics at the whole-body level while highlighting the crucial roles of innate immunity. In this light, the contribution of our model is its simplicity and focusing on the early blockade to the virus replication by the innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Interferons (IFNs) are the frontline defenders of the innate immune system, both interfering with infection of host cells and reducing viral replication inside infected cells. Recent models have explored the importance of innate immune response feedback pathways in determining the outcome of disease in individuals [ 22 • , 23 ]. The target-cell-limited modeling framework has been extended to analyze the effect of interferon-α therapy in treatment of Hepatitis C virus (HCV) infection [ 24 ] and to evaluate the relative importance of the two modes of IFN action (reducing production of virions by infected cells and reducing de novo rates of cell infection) [ 24 ].…”
Section: How Understanding Viral Kinetics and Immune Response Can Assist Development Of Antiviral Therapiesmentioning
confidence: 99%